Minimally invasive surgery for the management of major bile duct injury due to cholecystectomy. (14th February 2020) - Guerra, Francesco; Coletta, Diego; Gavioli, Manuel; Coco, Danilo; Patriti, Alberto
Abstract: Background: In recent years there has been a growing interest in the application of minimally invasive surgery in the management of cholecystectomy‐related injury to the biliary tract. The aim of this analysis was to identify and combine the available evidence on the argument, with particular reference to major injuries to the main bile duct requiring biliodigestive anastomosis. Methods: The PubMed/MEDLINE, Embase, and Web of Science electronic databases were queried through May 2019. Inclusion criteria considered all studies reporting detailed data about patients with bile duct injury following cholecystectomy receiving minimally invasive (both laparoscopic and robotic) surgical repair. Clinical outcomes data were pooled and analyzed. Results: A total of 31 studies reporting on the outcomes of 218 patients were eventually included in the analysis, whereby 148 patients with type D or E injury. Of these, there were 31 patients (21%) receiving direct bile duct repair and 117 patients (79%) undergoing bilioenteric reconstruction. Among patients with major bile duct injury, postoperative morbidity was 24%, being 12% the incidence of major complications and 6% the rate of patients requiring subsequent, further surgery. Conclusions: The absence of high‐level evidences precludes the possibility to draw definitive conclusions. However, the available data derived from a growing number of centers demonstrate that minimally invasive surgery may offer its well‐known advantages on postoperative outcomes also in the setting of severe iatrogenic injury to the bile ducts. Abstract : Highlight This analysis aimed to systematically review the available evidence on the application of minimally invasive surgery for the treatment of cholecystectomy‐related injury to the biliary tract. The data derived from a growing number of experienced centers show promising outcomes, even in the case of complex cases requiring biliodigestive reconstruction.